2018
DOI: 10.18502/kls.v4i5.2536
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ergonomic Risk Factors in Relation to Musculoskeletal Disorder Symptoms in Office Workers

Abstract: The development of technology has increased the number of activities workers are able to perform while using visual display units (VDUs), as well as the amount of time spent executing those activities; the developing technology, however, has also increased the probability of musculoskeletal disorders (MSDs), which can decrease a worker's productivity and result in a company's economic loss. Workers at PT. X use VDUs 8 hours per day. This research aimed to analyse the risk factors that are the likely cause of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 17 publications
1
15
0
6
Order By: Relevance
“…Regarding psychosocial risk factors, the present study identified job stress as a significant predictor of work-related musculoskeletal disorders. Similarly, Agnestifa et al 43 reported that job stress associated with self-reported WRMSDs. In the same way, the study done in India 10 and Malaysia 44 showed that psychosocial stress associated with WRMSDs.…”
mentioning
confidence: 91%
“…Regarding psychosocial risk factors, the present study identified job stress as a significant predictor of work-related musculoskeletal disorders. Similarly, Agnestifa et al 43 reported that job stress associated with self-reported WRMSDs. In the same way, the study done in India 10 and Malaysia 44 showed that psychosocial stress associated with WRMSDs.…”
mentioning
confidence: 91%
“…There have been a wide range of studies which support the considerable link between upper extremity impairments and socio-demographic factors, such as gender [3,23,24], age [11,25,26], marital status [21,26], level of education, and experience [27]. Scholars have also proved that factors relating to the physical work environments,including working hours [21,28], working posture [25,[28][29][30],shift work [26], rest break [30] as well as vibrations [31] importantly influence the experience of upper extremity disorders. Moreover, lifestyle factors, such as physical exercise [21,25], alcohol use [25,32] and smoking [33][34][35] and psychosocial-related factors including job dissatisfaction [36], job stress [30,37], and time pressure [3] have been confirmed as potential risks for the development of musculoskeletal pains.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have also proved that factors relating to the physical work environments,including working hours [21,28], working posture [25,[28][29][30],shift work [26], rest break [30] as well as vibrations [31] importantly influence the experience of upper extremity disorders. Moreover, lifestyle factors, such as physical exercise [21,25], alcohol use [25,32] and smoking [33][34][35] and psychosocial-related factors including job dissatisfaction [36], job stress [30,37], and time pressure [3] have been confirmed as potential risks for the development of musculoskeletal pains. However,in Ethiopia, studies involving tailors and the various adverse health outcomes they encounter because of the inherent nature of their jobs are inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Daika's research also concluded that the working postures have a mild correlation (r 0.407) with musculoskeletal disorder complaints. [21][22][23] Based on the explanation above, respondents who used laptops for more than six hours and in improper positions had the possibility of experiencing moderate to severe musculoskeletal complaints. In static muscle work, blood vessels are compressed by the increased pressure in the muscles due to contraction, causing blood circulation in the muscles to be disturbed.…”
Section: Discussionmentioning
confidence: 99%